2012
DOI: 10.1016/j.jvs.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Very Urgent Carotid Endarterectomy Confers Increased Procedural Risk

Abstract: More than 100 years ago, Trousseau reported migratory thrombophlebitis in cancer patients (Trosseau A, Lectures on Clinical Medicine, delivered at the Hotel-Dieu, Paris, London: New Sydenham Society; 1872; p 281-95). Subsequently, patients with DVT or pulmonary embolism (PE) have been shown to have up to a fourfold increased risk of cancer in the first year after the venous thromboembolic (VTE) event (Baron JA et al, Br J Cancer 2004;91:92-5). However, only one previous study has investigated the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 0 publications
4
84
3
1
Order By: Relevance
“…Strömberg et al 2 recommend against performing CEA within the first 48 hours, because of the high risk of procedural stroke observed in an earlier national audit. However, the current study did not assess procedural risk and the methodology was insufficient to draw any conclusions regarding the risks of early surgery.…”
mentioning
confidence: 99%
“…Strömberg et al 2 recommend against performing CEA within the first 48 hours, because of the high risk of procedural stroke observed in an earlier national audit. However, the current study did not assess procedural risk and the methodology was insufficient to draw any conclusions regarding the risks of early surgery.…”
mentioning
confidence: 99%
“…Multivariate ana lysis showed that time to intervention was the strongest determinant of risk of stroke or death, with an odds ratio of 4.24 (95% CI 2.07-8.70, P <0.001) for surgery within 2 days of the ischaemic event compared with surgery on days 3-7. 1 The increased risk was not attrib utable to a difference between centres, nor to variation in qualify ing events (TIA, minor stroke or major stroke) in those under going CEA at early or late time points. How ever, amaurosis fugax (transient monocular blindness) as the qualifying event was inde pendently associated with a lower risk of surgery complications.…”
Section: ''mentioning
confidence: 88%
“…The recent publication by Stromberg et al 1 provides convincing data to settle the ques tion of timing of surgery. The conclusion of their study involving 2,596 patients was that very early CEA, performed within 2 days of an ischaemic event (that is, on the day of symptoms or on either of the follow ing 2 days), has a detrimental effect on outcome.…”
Section: ''mentioning
confidence: 98%
“…Eine interessante und für den klinischen Alltag relevante Auswertung bezüglich der Komplikationsrate einer Karotis-Thrombendarterektomie (Karotis-TEA) in Abhängigkeit vom Operationszeitraum wurde aus schwedischen Registerdaten veröffentlicht [25]. Insgesamt wurde das Outcome nach Karotis-TEA bei 2596 Patienten untersucht, von denen 2000 prospektiv in die Datenbank eingeschlossen worden waren.…”
Section: Karotisstenoseunclassified